Preoperative assessment of haemostasis in patients undergoing stereotactic brain biopsy - Beynon, Christopher; Wei, Shilai; Radbruch, Alexander; Unterberg, Andreas; Kiening, Karl (Journal of clinical neuroscience, 2018)
Parenchymal hemorrhage is considered a major risk factor for perioperative morbidity in patients undergoing stereotactic brain biopsy. Studies on patients undergoing surgical procedures have suggested that evaluation of prothrombin time (PT) and activated partial thromboplastin time (aPTT) is of limited value with regard to prevention of haemorrhagic complications. However, this issue has not yet been addressed in patients undergoing stereotactic biopsy of intracranial lesions. We retrospectively analysed the medical records of 159 consecutive patients undergoing stereotactic biopsy of supratentorial intracranial lesions during a three-year period. Laboratory values (PT, aPTT, platelet count) were reviewed as well as clinical characteristics, modalities of surgical treatment, histopathological results and the postoperative course of patients. The overall diagnostic yield was 93.7%. Histopathological examination revealed glioma (WHOoI: 5, WHOoII: 25, WHOoIII: 23, WHOoIV: 65), lymphoma (n=14), inflammation (n=8) and other entities (n=6). Surgery-associated neurological deficits occurred in 7 patients (4.4%) and completely resolved in 6 of these patients. CT-confirmed intracranial hemorrhage occurred in 2 patients (1.3%) and in both cases, histopathological examination revealed glioblastoma. Results of hemostatic parameters (PT: 99+13%, aPTT: 24+3s, platelet count: 274+87103/μL) were within normal range values in all patients and did not correlate with postsurgical morbidity. Standard assessment of haemostasis seems to be of limited value in patients with intracranial lesions undergoing stereotactic biopsy. Further studies regarding the intratumoural vasculature’s impact on the risk of biopsy-related bleeding are necessary.